THE EFFECT OF MENOPAUSE ON NADPH OXIDASE LEVELS AFTER NON-SURGICAL PERIODONTAL TREATMENTS ON PATIENTS WITH PERIODONTITIS - Halef Dogan; Mahmut Kayaaltı; Vildan Bostancı (Cumhuriyet University, 2022)
ABSTRACT Objectives: This study evaluated the clinical parameters [ plaque index (PI), gingival index (GI), probing pocket depth (PPD), clinical attachment level (CAL) ] and the levels of Nadph Oxidase (NOX-1) in gingival crevicular fluid (GCF) samples of pre-menopausal and post-menopausal periodontally healthy and periodontitis patients. Materials and Methods: Study included pre-menopausal periodontitis 15, post-menopausal periodontitis 15, pre-menopausal periodontally healthy 15 and post-menopausal periodontally healthy 15; a total of 60 individuals were included. Results: Clinical periodontal evaluation indices in the 6th week after treatment were found to be statistically significantly lower than the initial values of PI, GI, PPD, CAL in the periodontitis groups(p<0.05). Pre-treatment baseline NOX-1 values were singificantly higher in both periodontitis groups than healthy groups (p<0.05). While the pre-menopausal and post-menopausal periodontitis groups before treatment had similar PI, PPD and CAL values, the GI was found to be significantly higher in the post-menopausal periodontitis group(p <0.05). While NOX-1 values in pre-treatment GCF samples were similar in pre-menopausal and post-menopausal periodontitis groups, NOX-1 values in the post-menopausal periodontitis group at the 6th week after treatment were found to be statistically higher than the pre-menopausal periodontitis group (p <0.05). Conclusion: According to the results of our study, oxidative stress that increases with menopause may negatively affect the healing potential after periodontal treatment. Accordingly, antioxidant supplementation can be predicted with hormone replacement during this period.